Characterization of laser beam transmission through a High Density Polyethylene (HDPE) plate. (February 2017) - Genna, S.; Leone, C.; Tagliaferri, V.
Abstract: Infrared (IR) light propagation in semicrystalline polymers involves mechanisms such as reflection, transmission, absorption and internal scattering. These different rates determine either the interaction mechanism, either the temperatures reached in the IR heating processes. Consequently, the knowledge of these rates is fundamental in the development of IR heating processes in order to avoid the polymer's damage and to increase the process energy efficiency. Aim of this work is to assess a simple procedure to determine the rates of absorbed, reflected, transmitted and scattered energy in the case of an unfilled High Density Polyethylene (HDPE) plate. Experimental tests were performed by exposing a HDPE plate, 3 mm in thickness, to a diode laser source, working at the fundamental wavelength of 975 nm. The transmitted power was measured by power meter, the reflected one by applying the Beer–Lambert law to sample of different thickness. IR thermal images were adopted to measure the absorbed ratio. The scattered ratio was measured by energetic balance, as difference between the incoming power and the other ratios. Finally, IR thermal images were adopted to measure the scattered ratio and to validate the procedure. Highlights: Interaction between Diode laser working at a wavelength of 975 nm and HDPE is investigated. Different procedures were adopted to estimate reflected, transmitted, absorbed and scattered power. The reflected power was estimated by a new procedure based on the Beer–Lambert law. The absorbed and scattered powers were measured by IR thermal images. It was shown that the scattered power has a magnitude of the same order of transmitted power.